Radio and television coverage of the Norrmalmstorg robbery - Comparisons with TT and Swedish press - Westerståhl, Jörgen; Andersson, Leif; Olsson, Claes-Olof; Jonasson, Margreth (University of Gothenburg, 1982)
This investigation on the news coverage of the bank robbery drama at Norrmalmstorg in Stockholm, August 1973, was made on the request of the Radio Committee. The aim was to illustrate whether the Broadcasting Corporation had fulfilled its obligation to illustrate contemporary events according to the contract between the state and the Broadcasting Corporation. As a material for comparison the Swedish daily press and TT:s (news agency) news telegrammes have been used.

På uppdrag av Radionämnden genomfördes denna undersökning av dels Sveriges radios nyhetsbevakning av, dels den svenska pressens behandling av händelserna i samband med bankdramat vid Norrmalmstorg i Stockholm under augusti 1973. Syftet med undersökningen av Sveriges radio var att belysa om företaget uppfyllt den i avtalet med staten och Sveriges radio stadgade skyldigheten att upplysa om nuets händelser. Som jämförelsematerial har därvid använts den svenska dagspressen och TT:s utgående nyhetstelegram.
Norrmalmstorgsdramats behandling i radio och TV - Jämförelser med TT och svensk press
Keywords: Media; Media; Information society; Informationssamhället; Social Sciences; Samhällsvetenskap